2021
DOI: 10.1590/s1679-49742021000300014
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência e fatores associados ao excesso de peso em adultos nas capitais e no Distrito Federal, Brasil, 2019

Abstract: Resumo Objetivo Analisar a prevalência e fatores associados ao excesso de peso nas capitais e no Distrito Federal, Brasil, 2019. Métodos Se Estudo transversal, com dados do inquérito Vigilância de Fatores de Risco e Proteção para Doenças Crônicas por Inquérito Telefônico, 2019. Calculou-se a prevalência de excesso de peso e sua associação com características sociodemográficas, comportamentais e situação de saúde, estratificada segundo sexo. Resultados A prevalência de excesso de peso foi de 55,9% (IC95% 54,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 16 publications
2
4
0
5
Order By: Relevance
“…The prevalence of overweight observed in more than half of the teachers is a relevant nutritional diagnosis for the health of this category of workers, since this condition represents a serious public health issue. These results are similar to those of other studies carried out with teachers before the pandemic in relation to excess body weight and also with the Brazilian population in general [16][17][18][19][20][21].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The prevalence of overweight observed in more than half of the teachers is a relevant nutritional diagnosis for the health of this category of workers, since this condition represents a serious public health issue. These results are similar to those of other studies carried out with teachers before the pandemic in relation to excess body weight and also with the Brazilian population in general [16][17][18][19][20][21].…”
Section: Discussionsupporting
confidence: 91%
“…When stratified by gender, it was observed that the prevalence of overweight was higher among men (58.2%) than among women (51.1%), with a statistically significant difference between them. The difference between women and men in relation to overweight was also found in a previous study that was representative of the Brazilian adult population; again in this case a prevalence of overweight among men was observed [21]. This may indicate that women would be more aware of the health benefits of caring for the body [22].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Aspects related to excess weight in Brazilian capitals, including those who self-declared as indigenous, revealed a prevalence of overweight in 55.9%, which was linked to arterial hypertension and diabetes mellitus 17,18 . The prevalence of arterial hypertension is close to 40% in women from Tribes Park, and there was a significant association between a group with a higher BMI and hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…The International Diabetes Federation (IDF) estimates that 463 million people worldwide have DM (9.3%), and that in the next 25 years, this number will reach 700 million, representing an approximate increase of 51% 1 . Brazil ranks fifth among the ten countries with the highest prevalence of DM in the world 1 , which is linked to risk factors prevalent among Brazilians, such as overweight, obesity and sedentary lifestyle 2 .…”
Section: Introductionmentioning
confidence: 99%